2009
DOI: 10.1021/cg900341r
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystallized Dinuclear−Mononuclear CuII3NaI and Double-Decker−Triple-Decker CuII5KI3 Complexes Derived from N,N′-Ethylenebis(3-ethoxysalicylaldimine)

Abstract: The syntheses and structures of a [2×1+1×2] cocrystal [{Cu II L 1 Na I (H 2 O) 2 }{Cu II L 1 } 2 ](NO 3 ) (1) and [3×1+5×1] cocrystal [{(Cu II L 1 ) 2 K I }(NO 3 )] • [{(Cu II L 1 ) 3 K I 2 (µ-NO 3 )}(NO 3 )] • 0.2H 2 O (2) derived from the hexadentate Schiff base compartmental ligand N,N′-ethylenebis(3-ethoxysalicylaldimine) (H 2 L 1 ) are described. Compounds 1 and 2 crystallize in triclinic P1 j and monoclinic P2 1 /c systems, respectively. The structure of 1 consists of the [Cu II L 1 Νa I (H 2 O) 3 ] + ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
68
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 86 publications
4
68
0
Order By: Relevance
“…The first of these shows interesting molecular recognition behavior towards a water molecule in the outer O4 coordination sphere forming the second complex site. This O4 pocket has also been used for the additional binding of s-or f-block metal ions leading to heterodinuclear Cu(II) complexes [17][18][19]. During our studies, we found that the reaction of the (±)-trans-1,2-cyclohexylidene bridged H2L 1 with Cu(NO3)2·3H2O (molar ratio 1:1) in methanol/tetrahydrofuran (v:v = 1:1) leads to a dinuclear Cu(II) complex.…”
Section: Synthesis Of the Ligands And Their Cu(ii) Complexesmentioning
confidence: 99%
“…The first of these shows interesting molecular recognition behavior towards a water molecule in the outer O4 coordination sphere forming the second complex site. This O4 pocket has also been used for the additional binding of s-or f-block metal ions leading to heterodinuclear Cu(II) complexes [17][18][19]. During our studies, we found that the reaction of the (±)-trans-1,2-cyclohexylidene bridged H2L 1 with Cu(NO3)2·3H2O (molar ratio 1:1) in methanol/tetrahydrofuran (v:v = 1:1) leads to a dinuclear Cu(II) complex.…”
Section: Synthesis Of the Ligands And Their Cu(ii) Complexesmentioning
confidence: 99%
“…Many mono/di/oligonuclear metal complexes have been reported from the following types of acyclic Schiff base ligands: (i) Single-compartment ligands (H 2 L Single ), obtained on [2+1] condensation of salicylaldehyde/2-hydroxyacetophenone/2-hydroxypropiophenone and a diamine [1][2][3][4][5][6][7][8][9][10][11]; Double-compartment ligands H 2 L OMe [1,[12][13][14][15][16][17][18] and H 2 L OEt [1,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] ligands, obtained on [2+1] condensation of 3-methoxysalicylaldehyde and 3-ethoxysalicylaldehyde, respectively, and a diamine. It has been established that H 2 L OEt ligands are something special because its O(phenoxo) 2 O(ethoxy) 2 compartment is strongly potential to act as a hydrogen bond acceptor with hydrogen bond donors such as water [1,[19][20][21][22][23][24][25]…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that H 2 L OEt ligands are something special because its O(phenoxo) 2 O(ethoxy) 2 compartment is strongly potential to act as a hydrogen bond acceptor with hydrogen bond donors such as water [1,[19][20][21][22][23][24][25][26][27][28][29][30][31], aquated proton [32,33], ammonium ion [22] and diprotonated diamine [34,35]. The metal complexes derived from H 2 L OEt ligands include mononuclear host-guest systems, dinuclear systems, double/triple/quadruple-decker compounds, supramolecular dimers and finite/infinite cocrystals [1,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. It is worth mentioning that a number of the metal compounds derived from H 2 L OEt ligands are weak interaction directed selfassemblies [1,[19][20][21][22][23][24][25]...…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13- 15,20] The significant difference between the two closely related ligand environments is surprising, and we would like to explore this area further. We were particularly interested in the 3d-3d complexes derived from new or unexplored H 2 Crystal structures of 2 and 5 are shown in Figures 1 and 2, respectively, while selected bond lengths and angles of these two compounds are listed in Tables 1 and 2, (2).…”
Section: Introductionmentioning
confidence: 99%